The social imaginary about alcohol in Ecuadorian films - Maldonado Espinosa, Mónica (2023)
This article proposes an analysis of how the consumption of legal and illegal drugs is projected in Ecuadorian fiction cinema. The objective is to interpret how cinematography creates an imaginary that reflects the Ecuadorian social and cultural conception in relation to drug consumption, mainly alcohol. We analyzed a sample of 12 films, selected from among those with the highest box office released between 2008 and 2018. An analysis methodology was developed that allowed us to identify the common characteristics in Ecuadorian fiction films. We focus the study on the qualitative research method. This allowed us to determine, as results, that the symbolic use of alcohol and drugs are presented as a social reflection of Ecuadorian current affairs. Some scenes in which the characters consume alcohol were analyzed, although this consumption does not provide a significant contribution to the plot of the films.